ANALISIS DINAMIKA KELOMPOK WANITA TANI PERKOTAAN D’SHAFA KELURAHAN MALAKA SARI JAKARTA TIMUR - Shafira Ayuning Lestari; Dika Supyandi (Universitas Galuh, 2023)
The women farmer group D'Shafa is one of the active farmer groups in Jakarta which is often used as a model in developing urban agriculture. This study aims to analyze the dynamics of the women farmer group D'Shafa in Malaka Sari, East Jakarta. All 11 members of D’Shafa Women’s Farmer Group were appointed as respondents in this research. This research uses qualitative design with descriptive analysis method. The results showed that the dynamics of the women's farmer group D'Shafa classified to the dynamics category with a total score of 1.203 and a percentage of 95.93%. The eight elements of group dynamics analyzed obtained dynamic results. The elements that achieve maximum total score are elements of group structure, group cohesiveness, and group atmosphere. This condition illustrates that the group dynamics of KWT D'Shafa are supported by organized structure and distribution tasks, so the interaction of group members becomes solid and familial.